Plasma neurofilament light in Huntington's disease: A marker for disease onset, but not symptom progression. (June 2021) - Parkin, Georgia M.; Corey-Bloom, Jody; Snell, Chase; Castleton, Jordan; Thomas, Elizabeth A.
Abstract: Objective: To investigate whether plasma NfL levels correlate with clinical symptom severity in premanifest (PM) and manifest HD (HD) individuals, and whether a NfL cut-point could distinguish PM from HD patients with reasonable accuracy. Method: 98 participants (33 control, 26 PM, 39 HD), underwent blood sample collection and clinical assessment, using both UHDRS and non-UHDRS measures, at one academic HD Center. Years to onset (YTO), probability of disease onset in 5 years, and predicted years until 60% onset probability were also calculated. NfL levels were measured using a Meso Scale Discovery assay. Results: Cohorts differed by age. NfL levels differed significantly across diagnostic groups and were significantly correlated with age. Age-adjusted NfL levels were not correlated with clinical measures in either HD or PM cohorts, but were correlated when cohorts were combined. In PM subjects, NfL levels correlated with YTO, probability of onset in 5 years, and years until 60% onset probability. Using ROC analysis, a NfL cut-point of <53.15 pg/ml distinguished HD from control; <74.84 pg/ml distinguished HD from PM. Conclusions: These findings implicate plasma NfL as a peripheral prognostic marker for premanifest-HD. Notably, we show that significant correlations between NfL and clinical symptoms are detected only when PM + HD subjects are combined, but not within HD subjects alone. To date, prior studies have investigated the clinical usefulness of NfL exclusively in merged PM + HD cohorts. Our data suggests a biasing of these previous correlations, and hence potentially limited usefulness of plasma NfL in monitoring HD symptom progression, for example, in clinical trials. Highlights: Plasma NfL is correlated with years to onset in premanifest HD (PM). Plasma NfL levels are significantly elevated following HD symptom onset. Plasma NfL is not correlated with symptom progression after HD symptom onset. Past studies of the mutation-positive cohort did not consider PM and HD separately. Plasma NfL may not be a useful biomarker in clinical trials of manifest HD subjects.